Keynesian economics in the stream of economic thought - McCracken, Harlan Linneus ([Baton Rouge] : Louisiana State University Press, 1961)
The book is divided into two parts: Part I. Pre-Keynesian Economists. Part II. The Keynesian System of Economic Thought.
Includes bibliographical references
rpm 09/11/2017
Loans
Keywords: Keynes, John Maynard; Commons, John R; Economics